Objective-C for absolute beginners iPhone, iPad, and Mac programming made easy - Bennett, Gary (Apress, 2011)
You have a great idea for an app, but where do you begin? Objective-C is the universal language of iPhone, iPad, and Mac apps, and Objective-C for Absolute Beginners, Second Edition starts you on the path to mastering this language and its latest release. Using a hands-on approach, you'll learn how to think in programming terms, how to use Objective-C to construct program logic, and how to synthesize it all into working apps. Gary Bennett, an experienced app developer and trainer, will guide you on your journey to becoming a successful app developer. If you're looking to take the first step towards App Store success, Objective-C for Absolute Beginners is the place to start.